SISTEM INFORMASI MANAJEMEN PADA KOPERASI HAYYATUN THOYYIBAH - Muslimah , Dinda Desmonda; Susanti , Deffy (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The Hayyatun Thoyyibah Cooperative faced significant operational constraints due to its manual management system, which resulted in a high risk of human error, inefficiency, and a lack of transparency. This research aims to design and develop a functional web-based Management Information System (MIS) to address these challenges. The development methodology employed is Extreme Programming (XP), which emphasizes adaptability and user collaboration, while system validation was conducted through black-box testing. The findings demonstrate the successful development of an MIS capable of managing membership data, savings and loan transactions, and reporting in an integrated manner. This system is proven to enhance operational efficiency, data accuracy, and transparency for its members, thereby providing an effective solution to the identified problems.